Draft Genome Sequence of Staphylococcus epidermidis (Winslow and Winslow) Evans (ATCC 14990) - Putonti, Catherine (Genome Announc, 2017)
Here, we report the draft genome sequence for the type strain Staphylococcus epidermidis (Winslow and Winslow) Evans (ATCC 14990). The assembly consisted of 2,457,519 bp with an observed G+C content of 32.04%. Thirty-seven contigs were produced, including two putative plasmids, with a 296.8× coverage and an N(50) of 180,848 bp.